Influence of entrepreneurial self-efficacy and entrepreneurship education on economics and business students’ entrepreneurial intention - Sang, Phung Khac; Tung, Phan Trong; Phuong, Mai Quynh; Lan, Do Thi Ngoc (Edelweiss Applied Science and Technology, 2026)
This study examines the impact of entrepreneurial self-efficacy and entrepreneurship education on the entrepreneurial intentions of economics and business students in Hanoi, Vietnam. A quantitative research design was employed using survey data collected from 250 students. The reliability and validity of the measurement scales were assessed through Cronbach’s alpha and exploratory factor analysis (EFA), followed by multiple linear regression to test the proposed relationships. The findings indicate that both entrepreneurial self-efficacy and entrepreneurship education significantly and positively influence entrepreneurial intention. Among these factors, entrepreneurial self-efficacy exerts a stronger effect (β = 0.460) than entrepreneurship education (β = 0.361). The model explains 49.8% of the variance in entrepreneurial intention, highlighting the critical role of both individual cognitive capability and educational support. This study contributes to the literature by reaffirming the relevance of Social Cognitive Theory in explaining entrepreneurial intention in an emerging economy context. It also provides practical implications for universities and policymakers to enhance entrepreneurial competencies and promote experiential learning approaches. Future research may extend this model by incorporating contextual and institutional factors across different educational and cultural settings.